Morphological, anatomical and isozyme variation among giant taro - SURATMAN SURATMAN; ARI PITOYO; SEPTIANA KURNIASARI; SURANTO SURANTO (Society for Indonesian Biodiversity, 2016)
Suratman, Pitoyo A, Kurniasari S, Suranto. 2016. Morphological, anatomical and isozyme variation among giant taro (Alocasia macrorrhizos) accessions from Central Java, Indonesia. Biodiversitas 17: 422-429. The objective of this study was to evaluate morphological, anatomical and isozyme variation among giant taro (Alocasia macrorrhizos (L.) G.Don) accessions from Central Java. Identification of morphological characters was done by direct observation of roots, leaves, stems, and corms. Anatomical characters were observed from both paradermal and transverse sections of leaf. Identification of biochemical markers was done by using peroxidase and esterase isozyme system. The genetic similarity among giant taro accessions was measured by using Group Average Clustering. The results of the analysis of variance revealed highly significant differences for majority of the tested morphological and anatomical characters suggesting that there was a high degree of diversity among the giant taro accessions. Isozyme polymorphism was observed in giant taro accessions using peroxidase (two banding patterns) and esterase (four banding patterns). Based on the dendogram, giant taro accessions were segregated into two major clusters. In Cluster I, the closest relationship were showed in KTN 2 and WNG 1 accessions from Klaten and Wonogiri that had 80.95% of similarity coefficient. The five accessions (SKA, SKH, WNG 4, KRA 3, KRA 4) from Surakarta, Sukoharjo, Wonogiri and some parts of Karanganyar were clustered separately as Cluster II with similarity coefficient of 50%.